Effect of Different Levels of Nitrogen, Phosphorus and Potassium Fertilizers on Yield of Cucumber (Cucumis sativus L.) Under The Climatic Conditions of Takhar Province - Andeshmand, Abdul Bari (Journal for Research in Applied Sciences and Biotechnology, 2024)
The experiment was carried out in the research farm of Agriculture Faculty, Takhar University under the title of the effect of nitrogen fertilizer with different amounts of phosphorus and potassium fertilizers on cucumber yield under the climatic conditions of Takhar Province, Afghanistan. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications and four treatments. Treatments T1 without of any fertilizer, T2 nitrogen 80 kg ha-1, phosphorus fertilizer 100 kg ha-1, and potassium fertilizer 85 kg ha-1. T3 nitrogen fertilizer 80 kg ha-1, phosphorus fertilizer 120 kg ha-1 and potassium fertilizer 95 kg ha-1. T4 nitrogen fertilizer 80 kg ha-1, phosphorus fertilizer 140 kg ha-1 and potassium fertilizer 105 kg ha-1. In the order of information related to fruit length, fruit diameter, weight per fruit, weight per plant, fruit yield per hectare in tons was registered. The maximum fruit length (19.39 cm), fruit diameter (4.80 cm), weight per fruit (184.87 gr), fruit weight per plant (2.86 kg) and performance per hectare (61.37 tons) in T4 with nitrogen fertilizer 80 kg ha-1, phosphorus fertilizer 140 kg ha-1 and potassium fertilizer 105 kg ha-1 were found, while the lowest recorded data was from T1 i.e. control. From this experiment, it can be said that the use of NPK fertilizer with the use of 80 kg of nitrogen fertilizer ha-1, 140 kg of phosphorus fertilizer ha-1 and 105 kg of potassium fertilizer ha-1 for cucumber cultivation caused better growth and performance in the field of Takhar University.